Making Homework a Catalyst of Teacher-Parents-Children’s Collaboration: A Teacher Research Study from an Elementary School in China - Gu, Huifen; Yin, Lidan; Li, Jiacheng (International Journal about Parents in Education, 2023)
Promoting teachers, parents and students to collaborate and participate in homework has important value to improve educational quality and develop a learning community. Based in the Chinese education context, the authors conducted an experiment of Happy Homework in one elementary school. The homework catalyzed the full participation of parents and cooperative innovation between the teachers and students. To investigate the outcomes and experiences of the project, the authors utilized a variety of research methods, such as questionnaires, onsite observation, interviewing and discussion with stakeholders, and transcript analysis. The authors found that collaboration among teachers, parents and students played a big role in the development of the students. It stimulated the students to perceive the quality of learning, and the students’ performance, learning quality, self-awareness, and social and emotional development was improved. In addition, a learning community was developed. Based on the initial case study, a series of follow-up research studies are being carried out in the case study school.